2023
DOI: 10.3389/fphar.2023.1201906
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CYP2C19 genotype on phenoconversion by concomitant medication

Laura M. de Jong,
Soukayna Boussallami,
Elena Sánchez-López
et al.

Abstract: Introduction: Pharmacogenetics-informed drug prescribing is increasingly applied in clinical practice. Typically, drug metabolizing phenotypes are determined based on genetic test results, whereupon dosage or drugs are adjusted. Drug-drug-interactions (DDIs) caused by concomitant medication can however cause mismatches between predicted and observed phenotypes (phenoconversion). Here we investigated the impact of CYP2C19 genotype on the outcome of CYP2C19-dependent DDIs in human liver microsomes.Methods: Liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 45 , 46 Investigations revolving around the classification of CYP2C19 activity have underscored a mere 40% alignment between genetically forecasted CYP2C19 phenotypes and actualized phenotypes, thereby unmasking the presence of phenotypic transformation. 47 Drug interactions with metabolic enzymes emerge as a prevailing factor instigating such metamorphoses, frequently perturbing enzyme activity via mechanisms of competitive inhibition. A vivid illustration can be found in scenarios involving lansoprazole and voriconazole treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 Investigations revolving around the classification of CYP2C19 activity have underscored a mere 40% alignment between genetically forecasted CYP2C19 phenotypes and actualized phenotypes, thereby unmasking the presence of phenotypic transformation. 47 Drug interactions with metabolic enzymes emerge as a prevailing factor instigating such metamorphoses, frequently perturbing enzyme activity via mechanisms of competitive inhibition. A vivid illustration can be found in scenarios involving lansoprazole and voriconazole treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that the phenoconversion effect might be dose-dependent [44]. Also, the phenoconversion was calculated based on the genetic phenotype, not on haplotypes due to the low number of patients; however, a study of de Jong showed that the phenoconversion might depend upon the specific polymorphism (e. g.,*1/*17 vs.*2/*17) [45]. Moreover, patients were not restricted to a diet, thus, nutrition may have affected enzyme inhibition/ induction.…”
Section: Strengths and Limitationsmentioning
confidence: 99%